Contribution of business angel investments: Evidence from Estonia - Tetsuya Kirihata (Journal of Capital Markets Studies (JCMS), 2022)
Purpose: This study aims to analyze the contribution of business angels (BAs), defined as wealthy individuals who provide risk capital to entrepreneurial firms without family connections, in Estonia, an emerging country in Eastern Europe. Design/methodology/approach: This study compared the data of the financial and non-financial performance of BA-backed firms with that of "twin" non-BA-backed firms, extracted from all Estonian unlisted firms using propensity score matching. Findings: The results of the comparative analysis showed that BAs were patient enough to allow their investees to spend for future growth rather than squeezing profit from increased sales. This is not patience without options for a BA in a situation in which the investee's sales are deteriorating, but rather deliberate patience in the presence of options for a BA where the investee's sales growth is increasing, contrary to conventional investor behavioral principles. It also showed that BAs' post-investment involvement did not make a direct contribution to their investees' sales, although BAs contributed to the sales increase through BA funding itself. Originality/value: This study has two unique research contributions. First, it shows that the patience of BAs was not a by-product but was intentional, and adds to the debate on whether BAs are patient investors. Second, there are only a few studies on the contribution of BAs to their investees in emerging countries; this study aims to help fill this research gap using the case of Estonia.
Keywords: G23; G32; L26; M13; 330; Business angels; Risk capital; Comparative analysis; Propensity score matching; Estonia; Emerging countries